A comparative study of parental rights in education as recognized in Pierce v Society of Sisters and subsequent US Supreme Court decisions up to 1969 - Dooley, James Patrick (University of Ottawa (Canada), 1973)
Abstract not available.
Keywords: Law.; Education, Policy.